Evaluation of the ground surface Enthalpy balance from bedrock temperatures (Livingston Island, Maritime Antarctic) - Ramos, M. (2019)
The annual evolution of the ground temperatures from Incinerador borehole in Livingston Island (South Shetlands, Antarctic) is studied. The borehole is 2.4 m deep and is located in a massive quartzite outcrop with negligible water content, in the proximity of the Spanish Antarctic Station Juan Carlos I. In order to model the movement of the 0◦C isotherm (velocity and maximum depth) hourly temperature profiles from: (i) the cooling periods of the frost season of 2000 to 2005, and (ii) the warming periods of the thaw season of 2002–2003, 2003–2004 and 2004–2005, were studied. In this modelling approach, heat gains and losses across the ground surface are assumed to be the causes for the 0◦C isotherm movement. A methodological approach to calculate the ground Enthalpy change based on the thermodynamic analysis of the ground during the cooling and warming periods is proposed. The Enthalpy change into the rock is equivalent to the heat exchange through the ground surface during each season, thus enabling to describe the interaction groundatmosphere and providing valuable data for studies on permafrost and periglacial processes. The bedrock density and thermal conductivity are considered to be constant and initial isothermal conditions at 0◦C are assumed (based in collected data and local meteorological conditions in this area) to run the model in the beginning of each season. The final stages correspond to the temperatures at the end of the cooling and warming periods (annual minima and maxima). The application of this method avoids error propagation induced by the heat exchange calculations from multiple sensors using the Fourier method.